INFLUENCE OF LOW TEMPERATURE INCUBATION ON DIAPAUSE INCIDENCE AND QUANTITATIVE TRAITS IN BOMBYX MORI L. - JAYASWAL, K.P.; RAUT, S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Influence of low temperature incubation on the quantitative traits of the larva and pupa and the incidence of diapause layings (egg batches) was studied in a multivoltine breed G-race of Bombyx mori. Incidence of diapause layings was brought down significantly during the winter season prone to it by incubating maternal layings at 18°C. With the increase/disease in larval period, larval weight, cocoon weight and shell weight, diapause incidence in layings oviposited by resultant moths also showed the same trend indicating a positive relationship with them.